The Influence Of Principal's Visionary Leadership Commitment Of School Culture Teachers on Junior High School Teachers' Work Productivity - Rusmina Yulianti; Edi Harapan; Muhammad Juliansyah Putra (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the Influence of Principal's Visionary Leadership, Teacher Commitment, and School Culture on the Work Productivity of State Junior High School Teachers. The research method used is a quantitative approach with a correlational survey design. The research sample consisted of randomly selected State Junior High School teachers in Kayuagung City District with a total of 151 respondents. Data was collected through a structured questionnaire that had been tested for validity and reliability. The results of the analysis showed that the visionary leadership of the principal had a positive and significant influence on the teacher's work productivity with a correlation value of 0.243 with a relationship percentage of 24.3% or close to 25%, while 75% was determined by other factors not mentioned in this study. In addition, teacher commitment and school culture have also been proven to significantly contribute to increasing work productivity. These findings underscore the importance of the role of school principals as visionary leaders in creating a supportive work environment, increasing teachers' professional commitment, and building a positive school culture to achieve optimal work outcomes. The implications of this study provide recommendations for education policy makers to strengthen the leadership capacity of school principals and build a conducive school culture.